Direct Wet Drum Seeded Rice An Emerging Resource Saving Technology for Rice Crop Establishment - B.M., Raghavendra; Singh, Y. V. (Indian Farming, 2015)
Direct sowing with drum seeder will help to tackle the labour shortage, increase the yield (8-11%), reduction in crop duration, drudgery and cost of cultivation in rice. Hence, all extension efforts should be taken up for its popularization through demonstration and training to farmers. Future strategy should be to increase row to row spacing to 25 cm from the existing 20 cm along with five drums which will help in easy mechanical weeding besides increase in unit area coverage.